PENINGKATAN SELF-ESTEEM MELALUI PROGRAM BIMBINGAN PSIKOSOSIAL BERBASIS CBT SISWI ANGKATAN I UPTD PSRWTS DINAS SOSIAL SUMATERA SELATAN - Rizki Amaliyah; Giska Muluddiani (Jurnal Edukasi Pengabdian Masyarakat, 2026)
ABSTRACT This community service activity aims to improve the self-esteem of the 1st Batch students of 2026 at UPTD PSRWTS Dinas Sosial Provinsi Sumatera Selatan, through a psychosocial guidance program based on Cognitive Behavioral Therapy (CBT). The main problem identified was low self-esteem among students, characterized by withdrawn behavior, self-doubt, and difficulty performing in public, which has the potential to hinder the success of the rehabilitation process. The urgency of implementing the program is based on the need to strengthen positive self-esteem to support rehabilitation success and readiness to return to society. The main challenges in program implementation are the limited number of professional psychology staff at the institution, the varied psychological conditions of students, and the need for adaptive approaches toward Generation Z. The implementation method consisted of three stages: preparation (integrated observation, weekly games, sharing sessions, and RSES measurement), implementation (group counseling based on CBT with cognitive restructuring techniques), and final evaluation (questionnaires and dreamboard). The results showed positive changes in performance, social, and physical aspects of self-esteem. The self-esteem enhancement model obtained includes three pillars: awareness of one's worth (living consciously), the desire for moral self-improvement (self-integrity), and self-assertiveness to dare to start new things. This program is recommended to be integrated into the routine training curriculum at the rehabilitation institution. Keywords: self-esteem; psychosocial guidance; cognitive behavioral therapy; social rehabilitation; adolescent